2018
DOI: 10.1016/j.jadohealth.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gender- and Sexuality-Based Harassment on Lesbian, Gay, Bisexual, and Transgender Substance Use Disparities

Abstract: Gender- and sexuality-based harassment at school independently or interactively produced LGBT disparities in substance use. Reducing these types of discrimination in schools will likely mitigate these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 36 publications
7
92
2
2
Order By: Relevance
“…Numerous studies have identified links between minority stress and increased likelihood of substance use. [13][14][15][16][17][18][19] Initially limited to sexual minority groups, this framework was expanded to gender minority populations 20 and suggests similar adverse health outcomes among gender minority individuals (e.g., transgender, gender nonbinary persons) may result from increased exposure to stigma and discrimination related to one's gender identity (i.e., someone's internal sense of their gender) and/or gender expression (i.e., how someone chooses to reflect their gender) compared to non-gender minority (i.e., cisgender 1 ) populations. 20,21 Research examining substance use across a diverse spectrum of sexual orientations and gender identities, however, remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified links between minority stress and increased likelihood of substance use. [13][14][15][16][17][18][19] Initially limited to sexual minority groups, this framework was expanded to gender minority populations 20 and suggests similar adverse health outcomes among gender minority individuals (e.g., transgender, gender nonbinary persons) may result from increased exposure to stigma and discrimination related to one's gender identity (i.e., someone's internal sense of their gender) and/or gender expression (i.e., how someone chooses to reflect their gender) compared to non-gender minority (i.e., cisgender 1 ) populations. 20,21 Research examining substance use across a diverse spectrum of sexual orientations and gender identities, however, remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although the present study did not have sufficient power to examine mediators, heavier smoking among transgender young adults may be due to transgender-specific stressors. For example, smoking is associated with later initiation of gender-affirming medical treatment (Menino, Katz-Wise, Vetters, & Reisner, 2018) and experiencing SGM identity-based harassment (Coulter, Bersamin, Russell, & Mair, 2018). Further research is needed to clarify the role of stress in the transgender community's high smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-lagged analyses indicate that as sexual orientation-related victimization declines across adolescence and into early adulthood, emotional distress decreases [26]. Cross-sectional studies are consistent with these findings [19], indicating, for example, that bias-based victimization mediates associations between sexual orientation and academic achievement and truancy among LGBQ youth [33] and between sexual orientation and gender identity and substance use for TGD youth [56,39]. …”
Section: Introductionmentioning
confidence: 94%